2021
DOI: 10.1111/jcmm.16309
|View full text |Cite
|
Sign up to set email alerts
|

The aberrant expression in epithelial cells of the mesenchymal isoform of FGFR2 controls the negative crosstalk between EMT and autophagy

Abstract: Signalling of the epithelial splicing variant of fibroblast growth factor receptor 2 (FGFR2b) triggers both differentiation and autophagy, while the aberrant expression of the mesenchymal FGFR2c isoform in epithelial cells induces impaired differentiation, inhibition of autophagy as well as the induction of the epithelial‐mesenchymal transition (EMT). In light of the widely proposed negative loop linking autophagy and EMT in the early steps of carcinogenesis, here we investigated the possible involvement of FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Then, we shifted our attention to EMT-related gene profile expressed in PDAC cells expressing different levels of FGFR2c. We found that the expression levels of the transcription factors Snail1, FRA1 and STAT3, which we previously identified as involved in FGFR2c-mediated EMT [ 8 , 21 ], overlapped with those of FGFR2c, appearing significantly higher in PANC-1 cells, compared to MiaPaCa-2 cells ( Supplementary Figure S1A ). Consistent with what was observed for the EMT-related transcription factors, the modulation of epithelial/mesenchymal markers compatible with EMT also appeared to overlap FGFR2c expression, displaying a more pronounced downregulation of the epithelial markers E-cadherin and a higher expression of the mesenchymal marker vimentin in PANC-1 cells compared to Mia PaCa-2 cells ( Supplementary Figure S1B ).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Then, we shifted our attention to EMT-related gene profile expressed in PDAC cells expressing different levels of FGFR2c. We found that the expression levels of the transcription factors Snail1, FRA1 and STAT3, which we previously identified as involved in FGFR2c-mediated EMT [ 8 , 21 ], overlapped with those of FGFR2c, appearing significantly higher in PANC-1 cells, compared to MiaPaCa-2 cells ( Supplementary Figure S1A ). Consistent with what was observed for the EMT-related transcription factors, the modulation of epithelial/mesenchymal markers compatible with EMT also appeared to overlap FGFR2c expression, displaying a more pronounced downregulation of the epithelial markers E-cadherin and a higher expression of the mesenchymal marker vimentin in PANC-1 cells compared to Mia PaCa-2 cells ( Supplementary Figure S1B ).…”
Section: Resultsmentioning
confidence: 84%
“…We have recently proposed a role of PKCε-mediated signaling not only in FGFR2c-mediated induction of EMT, but also in FGFR2c-dependent inhibition of the autophagic process in human keratinocytes [ 21 ]. Therefore, we investigated here the possible contribution of PKCε on autophagy also in the specific context of pancreatic cancer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative splicing is achieved by regulating the inclusion or exclusion of exons, which are then translated into protein sequences that perform different functions [ 32 ]. For example, alternative splicing of FGFR2 generates two transcripts, Ⅲb and Ⅲc, which promote or inhibit the EMT process, respectively [ 33 ]. In addition, alternative splicing of Bcl-x exon 2 produces two isoforms with opposing effects on cell survival: the anti-apoptotic long isoform (Bcl-xL) and the pro-apoptotic short isoform (Bcl-xS) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%